West elevation of 66 and 66 1/2 Beacon Street, January 14, 1973 - Waid, C. Franklin (Tufts Archival Research Center, 2005)
Street-level view northeast of the west elevation of 66 and 66 1/2 Beacon Street, located on the northeast corner of Beacon and Charles Streets. Signage adorns the west elevation of the building, which faces Charles Street. Commercial products are displayed in street-level windows along the Charles Street side of 66 1/2 Beacon Street. A traffic signal, street light and parking meter line the sidewalk along Charles Street. 7 3/8 x 9 3/8, 7 7/8 x 9 7/8 overall Photographs